2018
DOI: 10.33019/akuatik.v12i2.701
|View full text |Cite
|
Sign up to set email alerts
|

Struktur Komunitas Makrozoobentos Di Sungai Pakil Kabupaten Bangka

Abstract: Pakil River which is located in Paya Benua Village, West Mendo District, Bangka Regency. This river has an impact from mining activities which then affect the macrozoobenthos community. The purpose of this study was to determine the macrozoobenthic community structure in the Pakil River and determine the effect of water quality on macrozoobenthos in the Pakil River. The study was conducted in April 2018 in the waters of the Pakil River, Paya Benua Village, West Mendo District, Bangka Regency. The macrozoobento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…As for [3] who had conducted research at three locations in Banten Bay, reported that 32 species of fish were caught in Cengkok, then 58 species in Bojonegara, and 51 species in the coastal waters of Kemayungan-Linduk. In addition, several reports of research on the diversity of fish species have been recorded in coastal waters in Indonesia, which are much lower than on the Domas coast [15], [16], [17] [18]. Furthermore, for the observation of the largest individual yields, it is suspected that the species of Deveximentum interruptum and Caranx sexfasciatus have high adaptability and the Domas coastal waters may be an area for nurturing or foraging for these fish species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for [3] who had conducted research at three locations in Banten Bay, reported that 32 species of fish were caught in Cengkok, then 58 species in Bojonegara, and 51 species in the coastal waters of Kemayungan-Linduk. In addition, several reports of research on the diversity of fish species have been recorded in coastal waters in Indonesia, which are much lower than on the Domas coast [15], [16], [17] [18]. Furthermore, for the observation of the largest individual yields, it is suspected that the species of Deveximentum interruptum and Caranx sexfasciatus have high adaptability and the Domas coastal waters may be an area for nurturing or foraging for these fish species.…”
Section: Discussionmentioning
confidence: 99%
“…In the coastal waters of Muara Badak, Kutai Kertanegara, East Kalimantan, Carangidae species are also seen dominant [18], [3]. As for Leiognathidae and Clupeidae, it is also reported that members often place their members in coastal, coastal and mangrove waters [15], [22], [18], [3].…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini menunjukan bahwa tidak ada spesies yang mendominasi di kawasan Goa Kelelawar. Menurut Desinawati et al, (2018) indeks dominansi antara 0-0,5 menandakan tidak ada jenis yang mendominansi, sedangkan jika kisaran nilai antara 0,5-1 menandakan adanya jenis tertentu yang mendominansi. Namun jika dilihat dari individu yang ditemukan spesies L. blythii merupakan jenis yang paling banyak ditemukan hampir disetiap transek, tapi tidak mempengaruhi indeks dominansi pada kawasan Goa Kelelawar karena ada spesies lain yang jumlah individunya juga banyak ditemukan tapi tidak sebanyak L. blythii.…”
Section: Kekayaan Keanekragaman Kemerataan Dan Dominansi Jenisunclassified
“…Tingkat keanekaragaman yang rendah menunjukkan bahwa penyebaran individu tiap jenis cenderung tidak merata serta kondisi kestabilan komunitas yang diduga cenderung rendah. Hal ini disebabkan semakin kecil jumlah spesies dan adanya individu yang jumlahnya lebih banyak mengakibatkan terjadinya ketidakseimbangan ekosistem yang kemungkinan disebabkan adanya tekanan ekologi atau gangguan dari lingkungan di sekitar (Desinawati et al 2018).…”
Section: Indeks Ekologi Makrozoobentosunclassified